Ostrovy plovoucí k severu - Hron, Zdeněk (Klub přátel poezie, 1989)
Kniha obsahuje výběr z britské poezie 70. a 80. let 20. století (S. Heaney, D. Mahon, M. Longley, T. Paulin, G. Hill, T. Harrison, D. Dunn, D. Abse, J. Wainwright, J. Ash, P. Scupham, C. Raine, D. Sweetman, A. Motion, A. Stevensonová, F. Adcocková, A. Brackenburyová, G. Clarkeová, M. McCuckianová, P. Reading a J. Fenton).